A report on shaping branding: a comparative analysis of gactors influencing branding in Kenya and the USA- a case study of Square Pharmaceuticals Ltd. - Saswatee, Reevu (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.